(untitled) (Ustozlar uchun, 2026)
The translation profession is undergoing a profound transformation driven by rapid advancements in artificial intelligence, automation, and digital communication technologies. The emergence of neural machine translation and large language models has significantly altered traditional translation workflows, enabling faster and more cost-effective language services. As a result, the role of human translators is evolving from direct text translation to tasks that require higher levels of expertise, such as post-editing, localization, transcreation, and quality assurance.